Ultralow Specific Contact Resistivity in Metal–Graphene Junctions via Contact Engineering. Issue 1 (26th November 2018) - Passi, Vikram; Gahoi, Amit; Marin, Enrique G.; Cusati, Teresa; Fortunelli, Alessandro; Iannaccone, Giuseppe; Fiori, Gianluca; Lemme, Max C.
Abstract: A systematic investigation of graphene edge contacts is provided. Intentionally patterning monolayer graphene at the contact region creates well‐defined edge contacts that lead to a 67% enhancement in current injection from a gold contact. Specific contact resistivity is reduced from 1372 Ω µm for a device with surface contacts to 456 Ω µm when contacts are patterned with holes. Electrostatic doping of the graphene further reduces contact resistivity from 519 to 45 Ω µm, a substantial decrease of 91%. The experimental results are supported and understood via a multiscale numerical model, based on density functional theory calculations and transport simulations. The data are analyzed with regards to the edge perimeter and hole‐to‐graphene ratio, which provides insights into optimized contact geometries. The current work thus indicates a reliable and reproducible approach for fabricating low resistance contacts in graphene devices. A simple guideline for contact design that can be exploited to guide graphene and 2D material contact engineering is provided. Abstract : Well‐defined edge contacts to monolayer chemical vapor deposition graphene results in a 67% enhancement in current injection. Additional electrostatic doping yields edge contacts with a resistivity of 45 Ω µm, compared to 519 Ω µm for surface contacts. Experimental results are supported by a multiscale numerical model based on density functional theory calculations and transport simulations. A simple guideline for graphene contact design is presented.